Water-in-oil emulsion stability and demulsification via surface-active compounds: a review - Abdulredha, Murtada Mohammed; Hussain, Siti Aslina; Abdullah, Luqman Chuah; Tee, Lee Hong (Elsevier, 2022)
This paper aimed to review the research on emulsion formation, stability, chemical demulsification, and hydrophilic–lipophilic balance in chemical studies and other aspects related to emulsion thermodynamics. The global increase in energy demand pressures oil and gas producers to develop and explore a new source of energy. Crude oil is one of the indispensable sources produced from unconventional and conventional resources. It is accompanied by high water content during production activities, and this water is complex and has a high content of contaminants. This water is also produced in the form of foam or emulsion. Water-in-oil emulsion is considered as a common type in petroleum industry. Oil emulsion is very harmful due to the associated difficulties during the refining and transportation of crude oil and the limitation in the produced water discharge. The emulsion in petroleum industry is stable due to the natural surface-active compounds in crude oil. Thus, oilfield researchers need to study different utilization methods to demulsify emulsion. Chemical method is considered as an essential method in treating petroleum emulsion by using demulsifiers, such as non-ionic surfactant.